(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive analysis of mobile learning (m-learning) in English language education, focusing on its opportunities and challenges within higher education systems. Drawing on constructivist and sociocultural theories, the study examines how mobile technologies facilitate flexible, personalized, and context-based language learning. The article highlights key benefits such as increased accessibility, learner autonomy, motivation, and exposure to authentic language materials, while also addressing critical challenges including the digital divide, learner distraction, pedagogical limitations, assessment issues, and data security concerns. Based on theoretical insights and practical examples, the study argues for the integration of mobile learning within a blended learning framework to maximize its effectiveness. The findings suggest that with appropriate instructional design and institutional support, mobile learning can significantly enhance English language acquisition and better prepare students for global communication.